Iraq Reconstruction and Investment : Damage and Needs Assessment of Affected Governorates - World Bank Group (World Bank, Washington, DC, 2018)
The conflict inflicted by ISIS has forced over 5 million ordinary Iraqis to flee their homes, left schools destroyed and hospitals dysfunctional. Seven governorates have been fiercely affected while the entire country felt the shockwaves. During these times of despair, our neighbors and the global community have stood in solidarity with us. After the human suffering and enormous physical destruction that the conflict inflicted, it is now time to turn our gaze from the past to the future. It is time to rebuild the country and the citizens’ lives within. Today, where half of the displaced Iraqis have returned it is necessary to plan for recovery and reconstruction, to create enabling conditions for their return, and to restore livelihoods and service delivery for all in Iraq. The challenges ahead are to craft and execute a reconstruction plan that considers the aspirations of people as well as the constraints posed by time and funds. The preparation of a comprehensive reconstruction plan needs proper assessment of the damage, loss, and recovery needs. The Iraq Damage and Needs Assessment (DNA) is an assessment unprecedented in both its sectoral and geographic scope, covering damages, losses, and needs across 19 sectors in all conflict affected governorates in Iraq. Iraq’s Ministry of Planning took on this challenging task with the help of all line ministries of the Government, and with close collaboration with the World Bank. Scores of national and international experts worked around the clock to produce this assessment. The authors focused not only on the product, but also on the process. Data was gathered from the ground by national experts, from the air by satellites and on the internet by collecting publicly available data via social media analytics. Endless hours of review and validation were dedicated to ensure that the assessment of damages and needs was as robust and comprehensive as possible. The report has kept in mind what is desirable and what is possible. The objective is to estimate damages and to arrive at estimated needs to mobilize funds and to launch immediate recovery and incentivize private sector investments in the process.